Strategi Promosi Pariwisata Berbasis Ekonomi Kreatif Dalam Meningkatkan Daya Tarik Wisatawan (Studi Kasus Destinasi Wisata Pantai Rambang) - Susilawati, Susilawati; Zain, Rohaeniyah; Utomo, Danang Prio; Marselina, Selni (Universitas Hamzanwadi, 2025)
This research aims to ; find out creative economy-based tourism promotion strategies in increasing the tourist attraction of the Rambang Beach destination and the second objective is to find out the impact on the attraction or number of Rambang Beach tourists. The research method used in this research is qualitative descriptive research. Data sources were collected through primary data and secondary data. The subject of this research was carried out using snowball sampling. Using the snowball sampling technique, 33 village secretaries, tourism managers and the community were selected as informants.The research results also show that using alternative strategies along with creative economy-based tourism promotion strategies can increase the tourist attraction of Rambang Beach. To increase tourism there must be tourism that can attract visitors to come to the tourist spot. This tourism is by adding facilities with infrastructure that shows in the Rambang Beach tourist spot. So, from the village government's resources, they must have a strategy to increase tourist visitors who visit places on Rambang Beach.